May 2019 Internet Censorship in Indonesia: Critical Analysis of Its Policy Making Process (Administratio, 2020)
On May 2019 the Government of Indonesia imposed an internet censorship following Jakarta riot in response to general elections result. The government restricted some of the largest social media platforms which impacted almost all social media users across the country. The government believed that the policy was necessary to block the circulation of provocative contents which presumably escalate the riot. On the other hand, without valid justification, internet censorship is considered as human right violation. This paper aims to discuss the debate on whether the internet censorship policy on May 2019 was necessary and justified to impose. By employing qualitative approach through interviews with the government representatives, social media experts, and analysts, as well as utilizing resourceful data from Drone Emprit Academy (DEA), this paper presents the analysis of policy making process behind the implementation of internet censorship policy on May 2019 and brief evaluation on its effectiveness and consequences. The findings reveal that internet censorship policy on May 2019 was legally defective and improperly formulated. Even though it was effective to block the hoax circulation and prevented riot’s escalation, the policy was not supposed to impose at the first place due to lack of justification to derogate the internet freedom as part of human right. In the future, more specific regulations are needed as guideline for the government not to take sporadic internet censorship.